Solutions graphiques dans la cartographie des phénomènes quantitatifs - Cesar, Heldio (Cahiers de géographie du Québec, 1960)
The purpose of this paper is to present methods which will make easier the representation of quantitative phenomena in geographical cartography. The simultaneous use of certain combinations of the abacus presented here permits to eliminate completely long and fastidious calculations in the representation of quantities by figures and solids. The construction and the utilization of each abacus are successively explained.